2010
DOI: 10.1166/jnn.2010.2519
|View full text |Cite
|
Sign up to set email alerts
|

Biological Synthesis of Gold and Silver Nanoparticles Mediated by the Bacteria Bacillus Subtilis

Abstract: Biological synthesis of gold and silver nanoparticles was carried out using the bacteria Bacillus subtilis. The reduction processes of chloroaurate and silver ions by B. subtilis were found to be different. Gold nanoparticles were synthesized both intra- and extracellularly, while silver nanoparticles were exclusively formed extracellularly. The gold nanoparticles were formed after 1 day of addition of chloroaurate ions, while the silver nanoparticles were formed after 7 days. The nanoparticles were characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(38 citation statements)
references
References 0 publications
3
35
0
Order By: Relevance
“…Saifuddin et al (2009) found that exposure of culture supernatanant of Bacillus subtilis with microwave irradiation to silver ions lead to the formation of AgNPs with size in the range of 5 -60 nm. Reddy et al (2010) reported that there is extensive extracellular biosynthesis of AgNPs by using the same species B. subtilis.…”
Section: Nanomentioning
confidence: 99%
“…Saifuddin et al (2009) found that exposure of culture supernatanant of Bacillus subtilis with microwave irradiation to silver ions lead to the formation of AgNPs with size in the range of 5 -60 nm. Reddy et al (2010) reported that there is extensive extracellular biosynthesis of AgNPs by using the same species B. subtilis.…”
Section: Nanomentioning
confidence: 99%
“…More recently they also carried out a biological synthesis of gold and silver nanoparticles using the bacteria Bacillus subtilis. Gold nanoparticles were synthesized both intra-and extracellularly, while silver nanoparticles were exclusively formed extracellularly (Reddy et al, 2010). According to the Authors the nanoparticles were stabilized by the surface-active molecules i.e., surfactin or other biomolecules released into the solution by B. subtilis.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…They also plan to investigate these nanoparticles suitability for medical and diagnostic applications. Recently, methodologies for the biological synthesis of metal nanoparticles using microbes have also been described (Narayanan & Sakthivel, 2010;Kalishwaralal et al, 2010;Reddy et al, 2010). In addition Smyth et al, (2010b) reported on the production of selectively deuterated rhamnolipids and sophorolipids using deuterated substrates.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…The synthesizing process is low-cost and non-toxic [13,14]. The objective of this study is to demonstrate the feasibility of a bacterial/enzyme-based in vitro approach for the biosynthesis of gold nanoparticles from Enterobacteriaceae family.…”
Section: Introductionmentioning
confidence: 99%